2021
DOI: 10.1002/app.51436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thermal conductivity and esthetic quality of denture base resin composites with acrylic polymer and nanodiamonds

Abstract: The effect on the thermal conductivity and esthetic quality of acrylic denture base resins due to the addition of surface-carboxylated nanodiamonds (NDs) was evaluated using direct heat flux measurement and spectrophotometric measurement, respectively. The addition of NDs to the denture resin improved its thermal conductivity, which was highly depended on the ND content. The thermal conductivity increased significantly upon the addition of a small amount of NDs, followed by a gradual decrease with increasing N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…This can cause an increase in the temperature of the sample. The density of C. albicans ATCC 10231 has been reported before [40], and the thermal conductivity can be significantly modified by its surroundings [41]. In order to carry out numerical simulations to describe the temperature induced by light in the sample, a mathematical approach was proposed to involve a fractional Caputo derivative, where α is a fractional coefficient.…”
Section: Studies Of Ablation Effect Over C Albicans Atcc 10231 Biofilmsmentioning
confidence: 99%
“…This can cause an increase in the temperature of the sample. The density of C. albicans ATCC 10231 has been reported before [40], and the thermal conductivity can be significantly modified by its surroundings [41]. In order to carry out numerical simulations to describe the temperature induced by light in the sample, a mathematical approach was proposed to involve a fractional Caputo derivative, where α is a fractional coefficient.…”
Section: Studies Of Ablation Effect Over C Albicans Atcc 10231 Biofilmsmentioning
confidence: 99%
“…The DNT reinforcement mechanism is mainly based on mechanical interlocking and interfacial interactions, which are affected by the DNT’s morphology. Takada et al reported on acrylic denture base resins modified with NDs (0.014–1 wt.%) [ 30 ], and the results showed that a small amount of NDs could impart desirable thermal and esthetic properties to denture base resins. In addition, the ND denture base composites demonstrated antibacterial properties [ 19 , 28 ].…”
Section: Introductionmentioning
confidence: 99%